Crítica da produção da verdade no âmbito do processo judicial - Postal Junior, Jairo (2018)
This paper aims to investigate the intricate relationships between power and truth in the judicial process. In this context, based on the philosophy of Michel Foucault, the adoption by the Judiciary of a discourse of truth as a correspondence to the world of facts, will be demonstrated. As the goal of the discourse of truth is incompatible with the logic inherent in the process, it has the useful purpose of guaranteeing the legitimacy and maintenance of the State's power to decide all conflicts exclusively. In addition, it will be analyzed how the discourse of truth is sometimes used to extend state power beyond the limits of legality.